The Small-Conductance Ca2+-Activated Potassium Channel, Subtype SK3, in the Human Myometrium Is Downregulated in Early Stages of Pregnancy. (7th April 2013) - Rahbek, M.; Rosenbaum, S. T.; Dahl, M. J.; Klaerke, D. A.; Ødum, L.; Poulsen, S. S.; Larsen, T.; Bouchelouche, P.
Abstract : The human myometrium is mainly relaxed during pregnancy, but, up to term, contractions become more coordinated and forceful in order to initiate delivery. Small conductance Ca 2+ -activated K + channels (SK channels) in human myometrium have been shown to be downregulated in late pregnancy. The aim was to investigate the presence of SK2 and SK3 in the human myometrium from nonpregnant women, pregnant women at term, and pregnancies delivered preterm and, in addition, to characterize the time of downregulation of these channels. Using qRT-PCR, we observed significantly lower levels of mRNA for SK2 than for SK3 in the nonpregnant tissue. The mRNA levels of SK3 were significantly reduced in tissue from pregnancies at term and pregnancies resulting in preterm deliveries, whereas no downregulation for SK2 was observed. Western blotting confirmed the qRT-PCR results. Using immunohistochemical staining, both SK2 and SK3 were detected in endometrial glandular epithelium. We conclude that SK3 mRNA is downregulated early in pregnancy—at least among those that result in preterm deliveries. Furthermore, we find that SK channels are expressed not only in the uterine smooth muscle but also in the endometrial epithelium.